2018
DOI: 10.1098/rsif.2018.0229
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of the butterfly proboscis: the role of capillary forces

Abstract: The proboscis of butterflies and moths consists of two C-shaped fibres, the galeae, which are united after the insect emerges from the pupa. We observed that proboscis self-assembly is facilitated by discharge of saliva. In contrast with vertebrate saliva, butterfly saliva is not slimy and is an almost inviscid, water-like fluid. Butterfly saliva, therefore, cannot offer any viscoelastic adhesiveness. We hypothesized that capillary forces are responsible for helping butterflies and moths pull and hold their ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Understanding the mouthpart functionality of pollinating insects is of widespread interest to multiple disciplines (Lehnert et al, 2017;Li et al, 2016;Zhang et al, 2018). Here, we demonstrated that the lepidopteran proboscis displays a suite of mechanistic adaptations that relate to different feeding habits and enables feeding from floral tubes.…”
Section: Con Clus Ionsmentioning
confidence: 90%
“…Understanding the mouthpart functionality of pollinating insects is of widespread interest to multiple disciplines (Lehnert et al, 2017;Li et al, 2016;Zhang et al, 2018). Here, we demonstrated that the lepidopteran proboscis displays a suite of mechanistic adaptations that relate to different feeding habits and enables feeding from floral tubes.…”
Section: Con Clus Ionsmentioning
confidence: 90%
“…[ 126 ] Besides acquiring microfluidics from the environment, the proboscis is also a device for butterflies to release saliva for assembly and repair the separated proboscis or cleaning after feeding. [ 127 ] Inspired by the butterfly proboscis, Tsai et al fabricated the multilevel porous polyvinylidene fluoride (PVDF) fiber bundles through electrospinning to probes for a minute amount. Taking advantage of the electroconductibility of PVDF, the flexible PVDF fiber bundles can be manipulated by an electric field to detect the micro drops precisely.…”
Section: Bioinspired Superwetting Open Microfluidicsmentioning
confidence: 99%
“…The moth proboscis is a modified mouthpart that evolved from the two maxilla. When the moth first emerges from the pupal case, it unites the two galeae of the maxilla, and zips them together to form a central tube called the food canal, which serves as a drinking straw (Zhang et al, 2018). Both galeae are heavily muscularized and hydraulically controlled such that the proboscis is both flexible and actively actuated by muscles at its base and along its length (Wannenmacher and Wasserthal, 2003).…”
Section: Introductionmentioning
confidence: 99%